The planning system and land development in Malaysia: dominant town planning factors affecting private housing development / Ibrahim Mohd @ Ahmad - Ibrahim, Mohd@Ahmad (2009)
Research from various developed countries has demonstrated that the town planning systems affects housing development in terms of location, land use intensity, production costs and house prices, and has led to the emergence of housing problems. The town planning system in Malaysia which has been in practise since the 1920s might possibly have a similar impact on housing development here , but very few studies have dealt with this particular issue. The effects of town planning on housing land development could be related to the way planning authorities implement the planning systems, which includes the preparation of development plans, the interpretation of development plans into development plans, the interpretation of development plans into development control, and planning decision processes.